Synthesis and Properties of pH-, Thermo-, and Salt-Sensitive Modified Poly(aspartic acid)/Poly(vinyl alcohol) IPN Hydrogel and Its Drug Controlled Release - Lu, Jingqiong (Biomed Res Int, 2015)
Modified poly(aspartic acid)/poly(vinyl alcohol) interpenetrating polymer network (KPAsp/PVA IPN) hydrogel for drug controlled release was synthesized by a simple one-step method in aqueous system using poly(aspartic acid) grafting 3-aminopropyltriethoxysilane (KH-550) and poly(vinyl alcohol) (PVA) as materials. The hydrogel surface morphology and composition were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The thermal stability was analyzed by thermogravimetric analysis (TGA). The swelling properties and pH, temperature, and salt sensitivities of KPAsp, KPAsp/PVA semi-interpenetrating polymer network (semi-IPN), and KPAsp/PVA IPN hydrogels were also investigated. All of the three hydrogels showed ampholytic pH-responsive properties, and swelling behavior was also extremely sensitive to the temperature, ionic strength, and cationic species. Finally, the drug controlled release properties of the three hydrogels were evaluated and results indicated that three hydrogels could control drug release by external surroundings stimuli. The drug controlled release properties of KPAsp/PVA IPN hydrogel are the most outstanding, and the correlative measured release profiles of salicylic acid at 37°C were 32.6 wt% at pH = 1.2 (simulated gastric fluid) and 62.5 wt% at pH = 7.4 (simulated intestinal fluid), respectively. These results indicated that KPAsp/PVA IPN hydrogels are a promising carrier system for controlled drug delivery.